Alih Media Bacaan Siswa Alat Indra Manusia di Sekolah Dasar Melalui Pembuatan Komik - Tiaracindy, Tiaracindy; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ A making of comic from human sense is a form of learning for basic level of elementary school student as an effort to give a lesson for them to understand the function and part of the sense in themselves by transferring media of learning books to comic forms. This research uses descriptive methods by observing library data and reading resources from books. The making of this comic implements hybrid technique by combining traditional and digital ways, the traditional step is (a) determining theme of story, (b)creating of characters, (c) making of manuscript of story, (d) making sketch of characters, (e) thickening and coloring the characters, the digital step is (a) scanning the comic traditional, (b) combining the traditional and digital picture, (c) giving balloons of conversation, (d) making the cover of comic.Â  Key word: transfer media, comic, sense of human.